ANALISIS DAYA TERIMA KONSUMEN DAN KELAYAKAN BISNIS PRODUK MOUSSES BERDASARKAN PROSES BERBAHAN DASAR JAGUNG MANIS - Adlha, Syauqi Abdussyahid Fikar (2013)
This study has two variables, namely the analysis of consumer acceptance of products and business feasibility. The purpose of this study is: To find out the results of comparisons between products made from sweet corn mousses with mousses products made from fruits. To determine consumer acceptance and to determine the feasibility of the business mousses made from sweet corn. The method was used in this study, quantitative methods with experimental approaches and hedonic organoleptic test, test consumer acceptance and business due diligence. The results of this study showed that the concentration of materials mousses made from sweet corn is shaped creamy; Corn Products mousses compared with the control products were not significantly different from the difference in terms of taste, texture, color and aroma, making it easy mousses corn products acceptable to consumers, in terms of packaging and logo gives consumers a positive response; nutrient content of corn mousses have a better nutritional content than the control product; terms of business viability, mousses decent corn products to be developed with the acquisition of NPV valuation of Rp. 107.287.256. - Net B / C ratio = 5.9. BEP development time is the total cost of producing 32.346 units or with a value of Rp . 42.2 million. - Lack of product on corn mousses is located on a rather pale color and aroma less so out. Durability save mousses corn products have higher value as compared with the control product in terms of texture because corn has a lower acid content. Suggestions can be put forward from the results of this study are: To the culinary entrepreneurs pastry and desert areas need to develop local raw materials, because in addition has particularly economic value also has a typical value and competitive advantage in the marketplace. Keywords: Test Consumer Acceptance, Business Feasibility Pastry Products.